Developing annual cereal-legume mixtures in dairy goat farms in South-West of France, to improve protein self-sufficiency and reduce feeding costs - Jost J.; Tardif V.; Soulard T.; Guibert E.; Caillat H. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
Greater use of annual cereal-legume mixtures in grains is one solution to improve goat farms sustainability and protein self-sufficiency. Still few references are available about its use in dairy goat systems, despite its interests (low-input culture, resistance to bio-aggressors, crude protein yield). For 3 years (2016 to 2018), 113annual cereal-legume mixtures have been studied, both in commercial farms (REDCap: 101 samples) and in experimental unit (Inra Patuchev: 12 samples). Every sample represents an annual cereal-legume mixture produced by a breeder on his farm (plots of 8.8 ha +/-5.3), and given to goats. For each sample, we collect information on the sown mix, sowing rate, soil type, weather and technical route. We measure the yield, the proportion of each species and the quality of the harvested mix. Production costs are also estimated. They are often composed of triticale, peas, oats, faba beans, vetch and/or barley. 48% of annual cereal-legume mixtures are made of 3 or 4 species, with about 300 seeds/m² sown (+/– 72). On average, 3.5 t /ha (+/– 0.9) are harvested. It produces an interesting feed for animals, with 88.2% (+/– 0.04) of digestibility of organic matter,1 UFL (+/-0.04) and 15.7% (+/-2.8) of crude proteins. Annual cereal-legume mixtures represent 10% of goat requirements and 17% of protein requirements. An analysis of the database shows that i/mixtures with about 10% of fabaceae, ii/presence of faba bean (10-15 grain/m²) and iii/about 3-4 species secure yield and feeding value. These references will help goat farmers to develop the use of annual cereal-legume mixtures in dairy goat systems.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)